2016
DOI: 10.1080/21632324.2015.1053304
|View full text |Cite
|
Sign up to set email alerts
|

Migration, development and welfare: findings from a household survey in two selected villages in Bangladesh

Abstract: This paper contributes to the debate about the developmental impact of overseas migration using household level data from two selected villages in the southeastern region of Bangladesh. It argues in turn that remittances do contribute to household wealth accumulation but longer term investment in agriculture that can potentially lead to a change in agrarian structure is largely missing. An asset index is also employed to determine the welfare effects of both overseas and domestic migration. This paper begins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Duration of stay at the destination also plays a significant role in sending the remittances. These optimistic view supported by Mahapatro (2016) who found that households with overseas migrants for a relatively long duration are in fact better off. Present study also shows that frequency of such migration has a positive impact on sending more remittances comparatively to the people who have lesser frequency.…”
Section: Utilization Of Remittancesmentioning
confidence: 88%
“…Duration of stay at the destination also plays a significant role in sending the remittances. These optimistic view supported by Mahapatro (2016) who found that households with overseas migrants for a relatively long duration are in fact better off. Present study also shows that frequency of such migration has a positive impact on sending more remittances comparatively to the people who have lesser frequency.…”
Section: Utilization Of Remittancesmentioning
confidence: 88%
“…18 This reflects the relative returns from non-farm work in the area, and this may be another factor in explaining why land alienation is more prominent in Purbalach as compared with Hasanpur. In fact, in Purbalach, only overseas migrants of a longer duration could be differentiated among other households, which was not the case in Hasanpur (Mahapatro, 2016). However, this non-farm sector is highly differentiated, if we consider the lower quintile.…”
Section: The Nexus Between Land Migration and Rural Differentiation mentioning
confidence: 91%
“…Based on the household surveys and through construction of the asset index, significant differences in wealth (based on asset scores) were found between households with overseas migrants and others in both of the surveyed villages (Mahapatro, 2016). 8 In Purbalach, households with long-standing migrants overseas had significantly higher wealth indices.…”
Section: The Nexus Between Land Migration and Rural Differentiation mentioning
confidence: 99%
See 2 more Smart Citations